Polarization - F. Seling, Tenning; Wee, Cindy; Akir, Oriah; Wan Hassan, Sharifah Zakiah; Ramakrishnan, Prabha; Pereira, Helen; Ghazali, Azlina (Universiti Teknologi MARA, Sarawak, 2004)
Polarization refers to the tendency to look at the world in terms of opposites and to describe it in extremes- good or bad, positive or negative, healthy or sick, intelligent or stupid. It is often referred to as the fallacy of "either-or" or "black and white."